Legal Effects and Administration of Bank Acquisitions in Jordan: A Review of the Literature - Alshunnaq, Mueen (PRAWO i WIĘŹ, 2025)
Bank mergers and acquisitions (M&A) have become increasingly common in the financial services industry as banks seek to expand, diversify, and increase efficiency. These transactions have significant legal implications that must be navigated by both the acquiring and target banks. The legal effects of bank acquisitions span the entire transaction lifecycle. This paper provides a comprehensive overview of the key legal considerations involved. It begins by examining the regulatory approval processes and antitrust frameworks that govern bank M&A. The paper then looks at the legal steps of executing a bank acquisition, such as shareholder approvals, asset/liability transfers, and employee benefits. The discussion then shifts to the post-merger integration phase, highlighting the legal challenges that arise as the two organizations harmonize operations, compliance, and business models. The paper also explores potential litigation risks, including shareholder lawsuits or disputes with customers and vendors. Finally, the paper considers the longer-term legal impacts of bank acquisitions, including their effects on market competition, regulatory oversight, and the broader financial services landscape. Understanding these multifaceted legal dynamics is crucial for bank executives, legal counsel, and regulators to assess the viability and strategic implications of potential bank M&A activity.